2016
DOI: 10.1016/j.ccell.2016.02.007
|View full text |Cite|
|
Sign up to set email alerts
|

A SIRT2-Selective Inhibitor Promotes c-Myc Oncoprotein Degradation and Exhibits Broad Anticancer Activity

Abstract: Summary Targeting sirtuins for cancer treatment has been a topic of debate due to conflicting reports and lack of potent and specific inhibitors. We have developed a thiomyristoyl lysine compound, TM, as a potent SIRT2-specific inhibitor with broad anticancer effect in various human cancer cells and mouse models of breast cancer. Mechanistically, SIRT2 inhibition promotes c-Myc ubiquitination and degradation. The anticancer effect of TM correlates with its ability to decrease c-Myc level. TM had limited effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
244
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(257 citation statements)
references
References 57 publications
(82 reference statements)
13
244
0
Order By: Relevance
“…Recent reports using a selective SIRT2 inhibitor demonstrated that SIRT2 inhibition exhibits anti-tumor activity against breast cancer cells by degrading c-Myc oncoprotein. 8) Our results support this observation, as two selective SIRT2 inhibitors, RK-9123016 and SirReal2, 7) inhibited cell growth of human breast cancer MCF-7 cells accompanied by c-Myc degradation (Fig. 2), although their chemical structures are completely different.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Recent reports using a selective SIRT2 inhibitor demonstrated that SIRT2 inhibition exhibits anti-tumor activity against breast cancer cells by degrading c-Myc oncoprotein. 8) Our results support this observation, as two selective SIRT2 inhibitors, RK-9123016 and SirReal2, 7) inhibited cell growth of human breast cancer MCF-7 cells accompanied by c-Myc degradation (Fig. 2), although their chemical structures are completely different.…”
Section: Resultssupporting
confidence: 77%
“…8) Therefore, we examined the effect of RK-9123016 on cell viability of MCF-7 cells by measuring cellular amounts of ATP. Consistent with previous results, RK-9123016 as well as SirReal2 reduced the viability of MCF-7 cells in a concentration-dependent manner ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, SIRT2 inhibition in these BLBC cells caused the loss of the basal differentiation phenotype, colony-forming ability, and invasiveness characteristic of aggressive BLBC, ultimately resulting in diminished tumorigenic capability. Interestingly, a recent study demonstrated that selective SIRT2 inhibition has broad anti-cancer effects, in part by promoting the proteasomal degradation of the c-Myc oncoprotein (Jing et al, 2016). Notably in this study, several BLBC cancer cells also exhibited sensitivity to SIRT2 inhibition despite no observable decrease of c-Myc, suggesting that destabilization of other cancer-relevant substrates of SIRT2, such as Slug, may contribute to this anti-cancer effect in BLBCs.…”
Section: Discussionmentioning
confidence: 99%
“…S. Kim et al, 2011) or oncoprotein (P. Y. Liu et al, 2013) is controversial, many studies have observed anti-tumorigenic effects through SirT2 inhibition (Cheon, Kim, Choi, & Kim, 2015; Jing et al, 2016; Peck et al, 2010; Y. Zhang et al, 2009).…”
Section: Small Molecule Wild-type P53 Activatorsmentioning
confidence: 99%